Chronic kidney disease in adults aged 18 years and older in Chile: findings from the cross-sectional Chilean National Health Surveys 2009–2010 and 2016–2017 - Elena Pizzo; Magdalena Walbaum; Melanie Paccot (BMJ Open)
Objectives This study estimates the prevalence of chronic kidney disease (CKD) among Chilean adults and examines its associations with sociodemographic characteristics, health behaviours and comorbidities.Design Analysis of cross-sectional data from the two most recent large nationally representative Chilean Health Surveys (Encuesta Nacional de Salud, ENS) 2009–2010 and 2016–2017.Participants Adults aged 18+ years with serum creatine data (ENS 2009–2010: n=4583; ENS 2016–2017: n=5084).Primary and secondary outcome measures Reduced kidney function (CKD stages 3a–5) based on the estimated glomerular filtration rate (eGFR <60 mL/min/1.73 m2) was the primary outcome measure. Using the urine albumin-to-creatinine ratio (ACR ≥30 mg/g), increased albuminuria was ascertained among adults aged 40+ years with diabetes and/or hypertension. Both outcomes were analysed using logistic regression with results summarised using OR. CKD prevalence (stages 1–5) among adults aged 40+ years was estimated including participants with an eGFR of >60 mL/min/1.73 m2 but with increased albuminuria (stages 1–2).Results Overall, 3.2% (95% CI: 2.4% to 3.8%) of adults aged 18+ in ENS 2016–2017 had reduced kidney function. After full adjustment, participants with hypertension (OR: 2.37; 95% CI: 1.19 to 4.74) and those with diabetes (OR: 1.66; 95% CI: 1.03 to 2.66) had significantly higher odds of reduced kidney function. In ENS 2016–2017, 15.5% (13.5% to 17.8%) of adults aged 40+ years with diabetes and/or hypertension had increased albuminuria. Being obese versus normal-weight (OR: 1.66; 95% CI: 1.08 to 2.54) and having both diabetes and hypertension versus having diabetes alone (OR: 2.30; 95% CI: 1.34 to 3.95) were significantly associated with higher odds of increased albuminuria in fully-adjusted analyses. At least 15.4% of adults aged 40+ years in ENS 2016–2017 had CKD (stages 1–5), including the 9.6% of adults at CKD stages 1–2.Conclusions Prevention strategies and Chilean guidelines should consider the high percentage of adults aged 40 years and older at CKD stages 1–2.